Virtual reality application for hypermarket / Tang Wai Hung - Tang, Wai Hung (2005)
In these early years of 21st century, information technology is playing an important role in our lives. With the explosion of knowledge and information nowadays, Information Technology must be adopted to better manage of these aspect especially to increase the quality of virtual reality application. And this is why Virtual reality (VR) application for hypermarket comes in to bring a better experience in lecturing. Basically, "Virtual reality (VR) application for hypermarket' is application that can let user real-time interact with the system by the way in 3D. Therefore, user not only can get the information by word: user also can simulation navigate the virtual hypermarket environment. This VR system is creating by include user friendly concept for user easy to use, so is suitable for all level of people. This VR system provide many function to user, such as, user can stimulatingly travel around the virtual hypermarket environment, get a certain product price and location at this system without going to find at the hypermarket by themselves. Definitely you can buy your things and add into the shopping cart like the common e-commerce site! Beside this, the hypermarket administrator of this system can update and edit the database for stock maintenance. Just an authorize people can access this function for security method. With the application, user can navigate the virtual environment in the way of 3D. This "Virtual reality (VR) application for hypermarket" is more interactive and brings more effectiveness compare to a traditional e-commerce site.